A very rare case of cervicothoracic vertebral synostosis spanning eight adjacent segments: congenital vs acquired - BUĞDAYCI, ONUR (MARMARA UNIV, FAC MEDICINE, 2018)
An elderly female presented with acute post-traumatic neck pain. Cervical roentgenogram revealed a long-segment cervicothoracic vertebral fusion spanning 8 adjacent spinal levels. The patient was evaluated with computed tomography (CT) and magnetic resonance (MR) imagings of the spine, electromyography (EMG) and growth differentiation factor 6 (GDF6) gene mutation analysis. Imaging findings were atypical for congenital block vertebrae and there was no GDF6 mutation. A revision of very old medical records and patient's recollections revealed long-term stay in sanatorium for rehabilitation of chronic partially-treated brucella spondylodiscitis during adolescence. Block vertebrae spanning several levels have previously been reported; but, this is the first report of an acquired cervicothoracic fusion spanning 8 adjacent vertebral bodies.
Keywords: Cervicothoracic vertebral synostosis; Klippel - Feil syndrome; Magnetic resonance imaging; Brucellosis; Growth ifferentiation factor 6; KLIPPEL-FEIL-SYNDROME; CERVICAL-SPINE; ANOMALIES